A rapid immunochromatographic strip for neutralizing antibodies detection of foot and mouth disease virus serotype O. Issue 76 (13th October 2017) - Yang, Suzhen; Yang, Jifei; Sun, Yaning; Peng, Feng; Zhang, Shurong; Liu, Yunchao; Teng, Man; Zhao, Dong; Chai, Shujun; Zhang, Gaiping
Abstract : Based on the BSA-Pep antigen, a test strip was developed to evaluate the neutralizing antibody of serum samples from swine vaccinated with FMDV type O vaccine rapidly. The BSA-Pep used as a detector was labeled with colloidal gold. Abstract : Four peptides were designed and synthesized according to the main FMDV type O vaccine strains in china. Then the synthesized peptides were conjugated to carrier protein. The antigenicity of the artificial antigen was identified by dot-blot assay. Based on the BSA-Pep antigen, a test strip was developed to evaluate the neutralizing antibody of serum samples from swine vaccinated with FMDV type O vaccine rapidly. The BSA-Pep used as a detector was labeled with colloidal gold. Staphylococcal protein A (SPA) and anti FMDV antibodies were blotted onto the nitrocellulose membrane as the test and control lines, respectively. The strip assay could be performed within 5 min, which did not require any special equipment or skills. Through testing sera against various strains of FMDV type O, the sensitivity of the strip was determined to be 95% (38/40). There were no cross reactions to other virus antibodies, and no cross reactions in different serotypes of FMDV, the test strip can be used to detect FMDV type O antibodies only. The strip results were consistent with those of the existing commercial ELISA kits. In conclusion, the new strip was an acceptable method for surveying FMDV type O antibody titers in pigs.